Reconstructing Tolerance Education Through a Co-curricular “Social Laboratory”: A Theoretical Review of Intergroup Contact and Sosial Learning - Sarif Hidayat; Prayoga Bestari; Asep Mahpudz (The Innovation of Social Studies Journal, 2026)
Contemporary tolerance education in Indonesia faces a fundamental challenge: the discrepancy between the idealism of an inclusive curriculum and the reality of an increasingly polarized society. This article aims to reconstruct character education approaches by proposing a co-curricular-based "Social Laboratory" model as an alternative to conventional learning. Employing a conceptual analysis method on the "Breaking Down The Wall" program case study, this article synthesizes two primary theoretical frameworks: Gordon Allport’s Intergroup Contact Theory and Albert Bandura’s Social Learning Theory. The in-depth analysis demonstrates that co-curricular interventions are effective in reducing prejudice only if they satisfy four situational prerequisites: equal status, common goals, interdependent intergroup cooperation, and support from institutional authorities. These findings imply a need for school policy reform to institutionalize cross-identity encounters as a structured mandatory curriculum, thereby transforming students' tacit knowledge into tangible civic dispositions.